2007
DOI: 10.1017/s1368980007246580
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fruit and vegetable intake on the nutritional status and plasma homocysteine levels of institutionalised elderly people

Abstract: Objective: To determine the difference in the nutritional status of elderly people depending on their consumption of fruits and vegetables, and to study the possible association between the consumption of these foods and different cardiovascular risk factors, especially total plasma homocysteine (t-Hcys) levels. Design, setting and subjects: A cross-sectional study in 152 institutionalised older people from Madrid aged $ 65 years. Food and nutrient intakes were recorded over 7 days using the 'precise individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The consequence is a reduced intake of nutrients and bioactive substances whose positive effect was widely demonstrated in modulating some phenomena strictly linked to the aging process (such as inflammaging , oxidative stress, gut microbiota balance) [39]. A greater consumption of fruit and vegetables is associated with better food habits [40], and the literature suggests that these foods may be beneficial to elderly subjects, as well as a number of cross- sectional studies found a positive correlation between fruit and vegetables intake and bone mineral density [41], and a negative correlation with the onset of neurodegenerative disorders [42].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence is a reduced intake of nutrients and bioactive substances whose positive effect was widely demonstrated in modulating some phenomena strictly linked to the aging process (such as inflammaging , oxidative stress, gut microbiota balance) [39]. A greater consumption of fruit and vegetables is associated with better food habits [40], and the literature suggests that these foods may be beneficial to elderly subjects, as well as a number of cross- sectional studies found a positive correlation between fruit and vegetables intake and bone mineral density [41], and a negative correlation with the onset of neurodegenerative disorders [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, in agreement with epidemiology, DHA significantly benefited two measures of cognition in mild to moderate non-ApoE4 carriers [333]. High vitamin A and low homocysteine levels are related to a high intake of fruit and vegetables in elderly patients [246]. Fruit and vegetable juice consumption is also associated with reduced Alzheimer's disease incidence [334].…”
Section: Discussionmentioning
confidence: 79%
“…These protective factors are in most cases the obverse of the risk factors and include diets rich in fish or polyunsaturated fatty acids [241, 242], the Mediterranean diet [243] and the use of statins [244], which are counter to the effects of high cholesterol. A diet rich in fruit and vegetables is associated with reduced dementia incidence [245] and is able to sustain Vitamin A levels and reduce homocysteine levels in the elderly population [246]. High folate intake, which reduces homocysteine levels [247], and the use of nonsteroidal anti-inflammatories have also been reported to reduce risk [248].…”
Section: Resultsmentioning
confidence: 99%
“…Fruits and vegetables contain numerous micronutrients and functional ingredients with anti-oxidant properties which are helpful in keeping the homocysteine levels low thereby enhancing vascular health status. Increased fruits and vegetable intake has been effective in the improvement of plasma folate and homocysteine levels (Bermejo et al, 2007). In the other study, however, 4-week of increased fruits and vegetable consumption by 200 g/d (133 g/d for fruits and juice and 64 g/d for vegetables) was not sufficient to change plasma folate and homocysteine concentrations (Bogers et al, 2007).…”
Section: Discussionmentioning
confidence: 99%